Dynamics of Transformation in Turkey’s Foreign Policy - Asia Khatoon; Sajida Faraz; Manzoor Ahmad (ASIAN Journal of International Peace & Security (AJIPS), 2024)
Turkey is an economically and strategically significant country that is located in Eurasia and Western Asia. It has a unique synthesis of Western and Islamic culture and civilization. It focused on relations with the West and the European Union since 1924. However, under the government of Erdogan, its foreign policy is being shifted to the Muslim world and to purse a balanced approach to growing multilateralism. The paper is focused to exploring the growing changes in political, economic, social and diplomatic aspects of Turkish foreign policy. Turkey’s growing energy demands, expanding economic linkages and changing patterns in relations with regional and global countries and institutions are some prominent factors that depict a new form and picture of Turkey. This paper aims to discuss the underlying causes of political, economic, social and diplomatic change in Turkey as well as the country’s policies on various fronts. The ongoing transformation in Turkey and its impacts on regional and global levels have been analyzed. The descriptive-analytical method has been used to describe the policies and events and to analyze these with arguments.